Aplikasi Model Persamaan Struktural pada Program R (Studi Kasus Data Pengukuran Kecerdasan) - Rinaldi, Achi (Universitas Islam Raden Intan Lampung, INDONESIA, 2015)
Structural Equation Model (SEM) was known as powerfull and popular multivariate analysis technique. It provides a comprehensive method for the quantification and testing of theories. The ability of this model is to test model with multiple dependent that more powerfull than multiple regression, it’s also can make some simultaneously model in one form. Data was used from Holzinger and Swineford that measured intellegence in several indicator. This model was lack of form and performance that can be showed in value of Chi-square. Akaike Information Criterion (AIC) and Chi-square value for specificly in block “male” was less than “female”, so the result gave structural model for block male was better than female.